Políticas Educacionais Para O Ensino Médio: Confrontando Perspectivas - Santos, James Pereira Ruiz Sanches Dos [UNIFESP] (2018)
This Research Had The Objective Of Answering The Question "In What Sense Do Curricular Policies, With Their Ideological Constructions And Project Of Society, Take Into Account The Subjects To Which They Are Destined In The Different Contexts In Which They Are Formulated And Received?" To Answer The Main Question Above, Other Complementary Ones Were Necessary: A) What Are The Goals, Profiles And Objectives Sought By The Educational Policies For Brazilian High School Since Ldb / 96? B) What Are The Conceptions Of Youth Present In The Official Documents And What Are The Profile (S) Of The Brazilian Youth (S)? C) What Do Students Think About The Training Models To Which They Are Subjected By The Educational Policies Addressed To Them? To Answer These Questions, The Research Used Three Methodologies: 1. The Bibliographical Research To Discuss The Conceptual Difference Between Youth And Adolescence; To Characterize The Brazilian Youths In Order To Present Aspects Related To Education, Work, Family Life, Violence An